Antioxidant potential of Thymoquinone against Arsenic mediated neurotoxicity - Firdaus, Fakiha; Zafeer, Mohd Faraz; Anis, Ehraz; Fatima, Mahino; Hossain, M Mobarak; Afzal, Mohammad (Free Radicals and Antioxidants)
Introduction: Arsenic, an established poisonous metalloid has widespread occurrence in the environment which is posing a constant threat to health and survival of all living organisms. In view of arsenic induced oxidative stress and toxicity, this study focuses on the mitigatory role of thymoquinone, a major active component in the volatile oil of Nigella sativa (commonly known as black cumin); as its nutraceutical value can fulfil the demand of such dietary supplements in high risk population areas. Methods: In the current study, brain preparations of male wistar rats were used to assess different biochemical markers of oxidative stress and genotoxicity. Results: Significant and dose-dependent alterations in the level of enzymatic and biochemical biomarkers of oxidative stress were observed in the As-treated system. However, pre-treatment with thymoquinone brought about significant reduction in the As-induced neurotoxicity. Also, a significant decline in arsenic-induced DNA damage was recorded on pre-treatment with thymoquinone in comet assay. Conclusion: This study proves usefulness of antioxidant potential of thymoquione in mitigating the arsenic induced neurotoxicity.
Keywords: Arsenic; DNA Damage; Neurotoxicity; Oxidative Stress; Thymoquinone